(untitled) (Journal of the Bangladesh Agricultural University, 2017)
To evaluate the physicochemical characteristics of oilseeds, three varieties of mustard oilseeds were studied their seed weight, moisture, ash, carbohydrate, protein, fat, total energy and minerals composition of oil and cake. Among the varieties the highest thousand grain weight was found in BARI Sarisha-17 (4.24 g) and the lowest thousand grain weight was found in BARI Sarisha-15 (3.17 g). The highest moisture content was observed from BARI Sarisha-15 (4.52%); whereas the lowest moisture content was found in BARI Sarisha-17 (4.10%). The variety BARI Sarisha-17 contained significantly highest amount of oil (41.98%) whereas the variety BARI Sarisha-16 contained lowest amount of oil (40.95%). BARI Sarisha-16 contained highest amount of ash (14.20%). Significantly highest amount of protein was obtained from BARI Sarisha-15 (28.00%) and the lowest amount of protein obtained from BARI Sarisha-17 (22.57%). BARI Sarisha-17 contained highest amount of carbohydrate (18.85%), whereas BARI Sarisha-15 contained the lowest amount of carbohydrate (13.73%). BARI Sarisha-16 contained highest amount of Ca (2.52%) and Zn (66.80%). BARI Sarisha-15 contained highest amounts Cu (13.40%) and Fe (170.30%). Mustard varieties contained erucic acid (51.35-50.67%). Highest amount of total saturated fatty acid (TSFA) contained in BARI Sarisha- 15 (9.02%) and the lowest amount contained BARI Sarisha-16 (8.28%). Highest amount of total unsaturated fatty acid (TUSFA) contained in BARI Sarisha-17 (90.26%) lowest amount contained in BARI Sarisha-16 (87.04%). The highest amount of gross energy found from BARI Sarisha-15 (543.60 kcal/g; while lowest amount of gross energy recorded from BARI Sarisha-16 (531.20 kcal/g). Highest saponification value found in BARI Sarisha-17 (159.40) and lowest saponification value was found in BARI Sarisha-15 (157.6). The result of this research work confirms the mustard varieties seed to be of good quality and can be used for food preparation. The knowledge of this study could be utilized for various food preparation and selection for breeding purpose. J. Bangladesh Agril. Univ. 15(1): 27-40, January 2017